A dislocation-movement-and-void-growth-motivated ductile fracture criterion considering size effect. (1st December 2020) - Dong, Jun-Hong; Kong, De-Yang; Zheng, Zhi; Yang, Bo; Elchalakani, Mohamed
Abstract: A new ductile fracture criterion motivated by dislocation theory and void evolution is proposed to predict fracture initiation of high-strength steels, which also considers size effect. In this model, the maximum shear stress is the driving force of the dislocation movement. The high shear stress contributes to metal plastic deformation. The equivalent maximum normal stress accelerates void growth. It can promote the initiation and propagation of crack and deteriorate metal ductility. A ratio of the equivalent maximum normal stress to the maximum shear stress is developed in the ductile fracture model, representing the microscopic mechanism of void growth and dislocation movement. A series of fracture tests using different geometrical specimens are performed to cover a wide range of stress states and construct a three-dimensional (3D) experimental fracture locus. The typical uncoupled ductile fracture models based on stress state are evaluated. The results show that these models cannot agree well with the experimental data. This means that only considering stress state is not enough to predict the occurrence of fracture, mainly because size effect has a prominent influence on ductile fracture. Therefore, another parameter considering the size effect is introduced into this criterion. The comparison of numerical and experimental results indicates that the newly-proposed ductile fracture initiation model considering size effect can simulate precisely the occurrence of ductile fracture for high-strength steels.